Early buddhist art of China and Central Asia, volume three : the western Ch’in in Kansu in the sixteen Kingdoms period and inter-relationships with the Buddhist art of Gandhara. - Rhie, Marylin Martin. (Leiden ; Boston)
3.c. (lv, 544 s., 20 res., [395] s.)